African development indicators - United Nations Development Programme; World Bank. (New York : United Nations Development Programme ; Washington, D.C. : The World Bank, 1992)
Africa Development Indicators provides the most detailed collection of data on Africa available in one volume. It contains about 450 macroeconomic, sectoral, and social indicators, covering 53 African countries
"Builds upon the work undertaken in preparing African economic and financial data by extending coverage by three years and by including many more variables".
Includes bibliographical references: p. 363-365.
oif 02/08/16, ijb 21/02/2019
Loans
Keywords: Economic development; Economic indicators .; Social indicators .; Africa .